Performance Analysis of Reverse T-Shaped Tunnel Field Effect Transistor (RT-DG-TFET) Based Lable–Free Dielectric Modulation Detection of SARS-CoV-2 Virus. (1st November 2022) - Manikanta, K.; Nanda, Umakanta
Abstract : In this paper the performance of Reverse T-Shaped Double gate Tunnel field effect transistor is investigated (RT-DG-TFET)with respect to different bio molecules for application as biosensor. The proposed device is built in order to overcome the limitations of short channel effects (SCEs) in MOSFET devices. The recent outbreak due to Corona virus demanded the requirement of a lable free, highly sensitive, quick and meticulous biosensor for the detection of SARS-CoV-2 virus. This device study records the lable free electrical detection of SARS-CoV-2 virus using RT-DG-TFET that detects the virus because of the electrical properties (dielectric constant) of different bio molecules like protein, biotin, air, strepta, APTES, DNA etc. These are studied by using different dielectric modulation techniques in biosensor application. The etched nano-cavity implanted under the gate electrode first immobilizes the SARS-CoV-2 virus, which is subsequently used to identify it. The sensitivity and different analog/RF parameters are also investigated for different bio molecules. All these simulations are investigated in TCAD Sentaurus simulator.